EXPLORING THE POTENTIAL OF FE-CNT FOR HYDROCARBON GAS ADSORPTION - Yusfi, Meqorry
This research explored the potential of Fe-CNT in adsorbing C2H2, C2H4, and C2H6 gas, which was a novelty in this research. The first study's results were obtained by performing calculations using the Density Functional Theory (DFT) method on the Vienna ab-initio simulation package (VASP) software. Modeling was done on a five-unit SWCNT CNT (5.5) of 100 C atoms. The addition of Fe atoms was carried out in two ways, first by replacing one of the C atoms with Fe and, secondly, by placing a Fe atom on top of the C atom. The positions of the Fe atom above the C atom were carried out in three positions: bridge, top, and hollow. Of the three positions, the calculation results showed that the hollow position had the minimum interaction energy value (- 2.945 eV). The placement of Fe in the hollow position then interacted with C2H2, C2H4, and C2H6 gases. As a result of this interaction, the strongest adsorption energy value was obtained with good C2H2 gas, which was -3.23 eV. Furthermore, the calculation of Fe-CNT by applying uniaxial stress was also carried out to see the effect of the adsorption ability of Fe-CNT. In this calculation, SWCNT (10.0 ), which is a semiconductor, was used. The selection of this type of SWCNT intended to observe changes in the bandgap of SWCNT due to the applied uniaxial stress. The calculation results showed that applying uniaxial stress affects both positive and negative strain's total, gap, and adsorption energy. The resulting system energy had the same pattern; the more positive or negative the applied stress value, the greater the system energy (Es) value. Using a positive strain caused a more significant change in the gap energy, and applying a negative strain caused a minor change in the gap energy. After the uniaxial stress analysis, the effect on the adsorption ability of C2H2 gas was also observed. Along with the application of stress, the ability of Fe-CNT to adsorb C2H2 was also increased. The strongest adsorption energy value was -7% for compressive stress and 5% for positive stress. Compared with the pure CNT system, the adsorption energy on the Fe-CNT produced was stronger than pristine CNT. Fe-CNT exploration was also carried out experimentally by conducting in-situ heating of the material using the Hitachi H9500 High-Resolution Transmission Electron Microscope (HR-TEM). This experiment aims to observe the morphological changes in Fe-CNT due to heating at high temperatures. The first heating experiment was carried out at the initial position of Fe above the CNT, with the heating temperature reaching 410 oC. At this temperature, the Fe-CNT has melted and touched the filament. Before touching the filament, the Fe above the CNT changes its shape from elongated to oval. The diffraction pattern results show a change in structure from polycrystalline to amorphous.